Stalemate of the hydrological master variable? The challenge of implementing environmental flows in the Orange–Senqu basin. Issue 3 (3rd April 2022) - Mueller, André; Mirumachi, Naho; Tickner, David; Louw, Delana; Weston, Derek
ABSTRACT: In the face of declining rivers globally, the flow regime as the key hydrological determinant for healthy freshwater ecosystems is receiving unprecedented attention. This study investigates the challenge of implementing environmental flows in the Orange–Senqu basin in Southern Africa by assessing progress and its key factors during 1998 and 2013. Based on 22 interviews, the study shows that despite an advanced understanding of e-flows and its requirements, there have been effective implementation actions in only a few river systems to give effect to these e-flow requirements. Ineffective implementing institutions and a challenging basin context are more responsible than largely sufficient policies and legislation.